The Relationship Between Limited English Proficiency and Outcomes in Stroke Prevention, Management, and Rehabilitation: A Systematic Review - Clark, Jeffrey R.; Shlobin, Nathan A.; Batra, Ayush; Liotta, Eric M. (Frontiers in Neurology, 2022)
Introduction Individuals with limited English proficiency (LEP) face structural challenges to communication in English-speaking healthcare environments. We performed a systematic review to characterize the relationship between LEP and outcomes in stroke prevention, management, and recovery. Methods A systematic review was conducted using the PubMed, Embase, Scopus, and Web of Science databases. Titles and abstracts from articles identified were read and selected for full text review. Studies meeting inclusion criteria were reviewed in full for study design, aim, and outcomes. Results Of 891 unique articles, 20 were included. Eleven articles did not provide information about interpreter availability or usage, limiting the ability to draw conclusions about the effect of LEP on measured outcomes in these studies. Overall, studies demonstrated that English proficiency is associated with better outcomes in preventive aspects of stroke care such as stroke symptom awareness, anticoagulation maintenance, and knowledge of warfarin indication. Some acute stroke care metrics were independent of English proficiency in seven studies while other evidence showed associations between interpreter requirement and quality of inpatient care received. LEP and English-proficient groups show similar mortality despite greater lengths of stay and greater proportions of care in dedicated stroke units for LEP patients. Post-stroke quality of life can be worse for those with LEP, and language barriers can negatively impact patient and provider experiences of rehabilitation. Conclusions Stroke patients with LEP face barriers to equitable care at multiple stages. While some studies demonstrate worse outcomes for LEP patients, equitable care was shown in multiple studies frequently in the setting of a high degree of interpreter availability. Patients with LEP will benefit from tailored education regarding stroke symptom recognition and medication regimens, and from provision of translated written educational material. Inequities in inpatient care and rehabilitation exist despite similar mortality rates in four studies. Future studies should report interpreter availability and usage within LEP groups and whether patient interactions were language-concordant or discordant in order to allow for more generalizable and reliable conclusions.